2016
DOI: 10.1136/emermed-2015-205559
|View full text |Cite
|
Sign up to set email alerts
|

Does elevated urinary 5-hydroxyindole acetic acid level predict acute appendicitis in children?

Abstract: Urine 5-HIAA concentration measured in spot samples is not a reliable method for diagnosing acute appendicitis in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(40 citation statements)
references
References 20 publications
0
39
0
1
Order By: Relevance
“…Delayed diagnosis and treatment of these conditions may lead to a significant morbidity that may outweigh the harm caused by COVID-19 infection [ 3 ]. Acute appendicitis is one of the most common abdominal surgical emergencies in general with a 7% lifetime risk [ 4 – 7 ]. Eventhough antibiotics have been described as a type of therapy for uncomplicated appendicitis, surgery still remains the preferable treatment modality [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Delayed diagnosis and treatment of these conditions may lead to a significant morbidity that may outweigh the harm caused by COVID-19 infection [ 3 ]. Acute appendicitis is one of the most common abdominal surgical emergencies in general with a 7% lifetime risk [ 4 – 7 ]. Eventhough antibiotics have been described as a type of therapy for uncomplicated appendicitis, surgery still remains the preferable treatment modality [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies on adult patients which introduce new markers in the diagnosis of acute appendicitis have been conducted recently [5][6][7]. Some studies have also been conducted in the pediatric population [8][9][10][11]. Numerous parameters have been examined to support the diagnosis of acute appendicitis until today.…”
Section: Introductionmentioning
confidence: 99%
“…Enterochromaffin cells that contain large amounts of serotonin are mostly located in the distal appendix. Serotonin metabolite 5-hydroxyindoleacetic acid (5-HIAA) could therefore be a marker for acute appendicitis, but it has been shown that it is not a reliable method for diagnosing acute appendicitis in children [10].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the difficulty of obtaining a stool sample in the emergency department should also be considered. Urine 5-hydroxyindole acetic acid [ 6 ] and cortisol in hair [ 7 ] have also been evaluated. Considering that capillary sample processing requires specific equipment and trained personnel, the applicability in daily clinical practice of cortisol in hair is unfeasible.…”
Section: Introductionmentioning
confidence: 99%